MENINGKATKAN KREATIVITAS PADA ANAK - Sri Mulyati (Asian Journal of Innovation and Entrepreneurship, 2013)
Creativity is important in life, especially in early childhood because it can makepeople more productive. In addition to improving the quality of life as well as to facilitatethe search for a way out of a problem. Children should be given the power of creativitysince childhood, so they can have special skills. Skills are made not only of the new stuff,here children will be taught to cultivate creativity of junk so that goods that are not usedcan be re-processed into new items with new functions. Targets of this program is thechildren can take advantage of used goods such as aqua bottles to be used as a piggybank. Implementation of the program promote creativity in children through thefollowing steps. First children will be given theoretical skills. Second, children receivedetails of how to manufacture skills. This activity makes children can be good forcreativity by making bottles as new items are worth taking. During the programsimplemented are various obstacles such as at the time of extension of the theory to thekindergarten children who need extra patient gives recognition while playing so they donot get bored. To overcome this, we tried to blend with the children beforehand, sothat they know and love us, and that we are easy to explain.